A capability perspective on service provision in project-based organisations. (7th April 2021) - Zighan, Saad; Al-Kalha, Ziad; Bamford, David; Reid, Iain
The theoretical underpinnings related to the required capabilities of service provision remain under development. Hence, this study aims to explore the pathway for service business development in project-based organisations. Using a qualitative case study approach, 30 interviews were conducted with project-based organisations from five different industries in eight countries. Thematic analysis techniques were used to analyse the data. Upon which, this study identifies the essential capabilities for the successful implementation of servitisation strategies; these direct the projects to be customer orientated and sustain the core operations of service provision. Adopting dynamic capability theory, the study offers a roadmap for how project-based organisations develop and gain these capabilities. The results indicate a difference between the companies in developed as opposed to developing countries, when building their capabilities. The study contributes to the body of knowledge and proposes to decision makers the use of effective processes to help align project operations and service provision activities. It explains how project-based organisations reconfigure their resources to build essential capabilities to provide services. Moreover, the study highlights the differences between developed and developing countries in terms of the capabilities used and how they develop them.